Assessing the Effect of a Major Quantitative Locus for Phosphorus Uptake (Pup1) in Rice (O. sativa L.) Grown under a Temperate Region - Navea, Ian Paul; Han, Jae-Hyuk; Shin, Na-Hyun; Lee, O New; Kwon, Soon-Wook; Choi, Il-Ryong; Chin, Joong Hyoun (Agriculture (Basel), 2022)
Water and phosphorus (P) fertilizer are two of the most critical inputs in rice cultivation. Irrigation and chemical fertilizers are becoming limiting factors under climate change and urbanization, which is leading to significant losses in yield. The Pup1 quantitative trait locus (QTL) confers tolerance to P starvation through enhanced early-stage root vigor and P uptake in indica rice grown in the tropics. Whether the QTL works in temperate rice genetic backgrounds grown in temperate regions remains to be elucidated. To address this question, we introgressed the Pup1 QTL into three temperate rice varieties—MS11, TR22183, and Dasanbyeo—using marker-assisted backcrossing and high-density genotyping. The selected lines all harbored the full Pup1 QTL with recurrent parent genome recovery rates ranging from 66.5% to 99.8%. Under the rainfed and P non-supplied conditions, Pup1 introgression lines did not show clear advantages over the recurrent parents in terms of vegetative growth and grain yield per plant, but exhibited enhanced yield responses to P application, except in Dasanbyeo, which a temperate rice that is genetically similar to indica. Our results suggest that Pup1 confers enhanced P uptake in temperate rice and that the efficacy of Pup1 might depend on the subspecific genomic background of the rice, whether it is japonica or indica.